Meningkatkan Pemahaman Masyarakat Dalam Penggunaan Bahasa Inggris Pada Bidang Sains Melalui English On Street - Zaitun Qamariah; Hadma Yuliani; Syahrul Mubaroq (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to help the community improve their understanding of the use of English in the field of science in everyday life. The analytical method used in this service is the descriptive method. The data collection techniques used are observation, question and answer, and documentation. Based on the results of the community service carried out, it can be concluded that the activities were carried out starting with preparation (placing banners and distributing brochures so that the community would know information about the activities being carried out), core activities (games related to the use of English in the field of science owned by the community and providing food free light as a reward for participants to be more confident in developing skills in the field of science) as well as a closing activity (photo with visitors who participated in the activity).